SOME FEATURES OF DESIGNING TRUSSED RAFTER OF DOUBLE ANGLES - O. Yu. Marakhina; D. A. Kuzmin (Вестник СибАДИ)
The article deals with questions of the origin and influence bending moments on the bearing capacity of rods of the trusses of double angles on gusset plates. The results of the research with requirements of current codes of practice in construction are compared. Additional conditions for the emergence of complementary internal forces in trusses, besides the generally accepted ones, are determined. According to the results of a research, an engineering method for taking into account the influence of bending moments in the rods of trusses of double angles is proposed in checking calculations and designing trusses.